In Search of Competitiveness for An Apparel Manufacturing SME - Fernando, W.A. (2013)
Present day entrepreneurs are becoming the driving force of economies in developed and developing countries. As their enterprises grow they fail to succeed by staying competitive or they struggle to achieve growth by further developing the businesses. This is due to the inability to integrate opportunity seeking and advantage-seeking behaviours to gain sustainable competitive advantage.